Doświadczenie bezradności cierpienia dziecka w narracjach słuchaczy studiów podyplomowych Profilaktyka przemocy seksualnej wobec dzieci i młodzieży - Barbara ADAMCZYK (Edukacja Ustawiczna Dorosłych)
The article addresses issues related to the experience of helplessness of a child’s suffering. The theoretical part presents the perspective of understanding the helplessness of a child experiencing sexual violence. The methodological part introduces the basic assumptions of the research project. The subject of the study was the helplessness of a victim of sexual violence, and the purpose was to identify significant determinants showing the helplessness of suffering of a child experiencing sexual violence and their description in the experience of study participants. The study used the narrative method following content analysis. The research problem took the form of a question: What is the experience of helpless suffering of a child in the narratives of post-graduate students preparing to work with an abused child? The research was conducted in 2019 among 23 post-graduate students preparing for counseling work. Obtained research results have allowed the emergence of subcategories within the examined categories that show the specificity and value of the helplessness of the suffering of the child described by the respondents - victims of sexual violence. In addition, the conclusions of the study are valuable for pedagogical practice, especially in the scope of enriching the educational offer for the teaching profession and teacher in relation to diagnostic, intervention and support activities for people with experience of violence.